2012
DOI: 10.1111/j.1532-5415.2012.04191.x
|View full text |Cite
|
Sign up to set email alerts
|

Picture‐Based Memory Impairment Screen for Dementia

Abstract: OBJECTIVES To develop and validate a picture-based memory impairment screen (PMIS) for the detection of dementia. DESIGN Cross-sectional. SETTING Outpatient clinics, Baby Memorial Hospital, Kozhikode city in the southern Indian state of Kerala. PARTICIPANTS Three hundred four community-residing adults aged 55 to 94 with a mean education level of 8 years; 65 were diagnosed with dementia. MEASUREMENTS PMIS: a culture-fair picture-based cognitive screen designed to be administered by nonspecialists. Diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(82 citation statements)
references
References 27 publications
3
79
0
Order By: Relevance
“…A hospital based study by Dr Joe Varghese et al in Kerala for the validation of PMIS showed a prevalence of 21.3% among the elderly in 2010. 10 The fact that elderly persons with visual and hearing impairment were excluded could have led to a slightly higher estimate. Even so, the prevalence obtained in the study is within the range of prevalence rates reported from other studies conducted in India.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A hospital based study by Dr Joe Varghese et al in Kerala for the validation of PMIS showed a prevalence of 21.3% among the elderly in 2010. 10 The fact that elderly persons with visual and hearing impairment were excluded could have led to a slightly higher estimate. Even so, the prevalence obtained in the study is within the range of prevalence rates reported from other studies conducted in India.…”
Section: Discussionmentioning
confidence: 99%
“…Previous community-based studies estimate the prevalence of dementia among the elderly to range from 1.5% to 14.89%. 7,9,10,[18][19][20][21]23 Considering a prevalence of 5% with 3% absolute precision at 95% confidence interval our sample size was calculated to be 202. 20 We included all older adults above 60 years who were permanent residents of the area (at least one year of residence).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Participants were prospectively recruited from neurology clinics at the Baby Memorial Hospital, Kozhikode, between September 2008 and March 2012. 4 Referral reasons were cognitive complaints or other neurological symptoms including headache, stroke, or neuropathy. Cognitively normal controls were recruited from participant relatives or individuals attending the clinic for noncognitive symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…I'm enthusiastic about Rosli et al's (Rosli et al, 2017) comparison of the Identification and Intervention for Dementia in Elderly Africans (IDEA) Cognitive Screen developed for dementia in a low-literacy settings (Gray et al, 2014) and the Picture-Based Memory Impairment Scale (PMIS) developed for those with little to no formal education (Verghese et al, 2012) to the Mini Mental State Examination (Folstein, Folstein, & McHugh, 1975). Their results, from Malaya, Malaysia suggest clinical equivalency without educational bias.…”
Section: Fellow Clinical Gerontologistsmentioning
confidence: 99%